1996
DOI: 10.1016/0014-5793(96)00070-1
|View full text |Cite
|
Sign up to set email alerts
|

A functional Spo0A is required for maximal aprE expression in Bacillus subtilis

Abstract: The initiation of sporulation in Bacillus subtilis is under control of the transcriptional factor Spo0A. Most Spo0A mutants fail to initiate the sporulation process and aH the sporulation initiated processes such as the synthesis of subtilisin.However, the product of spoOd9V, one of the several spo0A mutants characterized, distinguishes itself in the fact that, while it appears to effectively repress abrB, it fails to activate the spollA operon. The aim of this study was to examine the effect of the spoOA9V mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 24 publications
(28 reference statements)
2
9
0
Order By: Relevance
“…2). These results are in good agreement with the fact that a major control of aprE expression occurs at initiation of transcription through the AbrB\SpoOA switch (Olmos et al, 1996).…”
Section: Construction and Transcriptional Control Of Apre-lacz Fusionssupporting
confidence: 88%
“…2). These results are in good agreement with the fact that a major control of aprE expression occurs at initiation of transcription through the AbrB\SpoOA switch (Olmos et al, 1996).…”
Section: Construction and Transcriptional Control Of Apre-lacz Fusionssupporting
confidence: 88%
“…We compared the promoter strength of cry3Aa with that of the wellknown aprE promoter (Ogura et al, 2004). It has been reported that protein expression from the aprE promoter increased significantly in cells with the degU32 genetic background (Olmos et al, 1996). Our results showed that lacZ expression induced by the cry3Aa promoter was 3.86-fold higher than the expression induced by the aprE promoter in wild-type and 3.58-fold less than that of aprE promoter in degU32 cells (Table 2).…”
Section: Screening Of Cry Promoterssupporting
confidence: 34%
“…In agreement with this observation, most genes that are positively regulated by DegU-P are known to be repressed by other regulatory proteins during exponential growth. Transcription of amyE is repressed by CcpA in the presence of glucose (Henkin et al 1991) and aprE is transcriptionally repressed by the transient phase regulators ScoC (Henner et al 1988a;Kallio et al 1991), AbrB (Ferrari et al 1988;Olmos et al 1996) and SinR (Olmos et al 1997). Negative regulation by ScoC has also been described for nprE (Kallio et al 1991), and expression of bglS was found to be regulated in response to the level of GTP in the cell, most probably also mediated by AbrB (Stu¨lke et al 1993).…”
Section: Resultsmentioning
confidence: 86%